2022
DOI: 10.3390/biom12020306
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to Bacterial Biofilms and Their Proteases, and Their Roles in Host Infection and Immune Evasion

Abstract: Bacterial biofilms represent multicellular communities embedded in a matrix of extracellular polymeric substances, conveying increased resistance against environmental stress factors but also antibiotics. They are shaped by secreted enzymes such as proteases, which can aid pathogenicity by degrading host proteins of the connective tissue or the immune system. Importantly, both secreted proteases and the capability of biofilm formation are considered key virulence factors. In this review, we focus on the basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 156 publications
(170 reference statements)
1
14
0
Order By: Relevance
“…In this study, we found that when hfq was deleted, the expression of many enterotoxin genes in bacteria, such as nheA , nheB , entFM , entD 1, entD 2, and hbl C, was significantly increased at the transcriptional level ( Figure 6B ), which to some extent enhanced bacterial virulence ( de Maagd et al, 2003 ). In addition, the deletion of hfq also led to a significant increase in the amount of bacterial biofilm formation ( Figure 3B ), and the ability to form biofilms is also considered to be a key virulence factor in a variety of bacteria ( Ramírez-Larrota and Eckhard, 2022 ). Environmental adaptability can help bacteria resist antibiotics and the host’s immune system, which facilitates bacterial survival and infection in the host, ultimately leading to host death ( Al Safadi et al, 2012 ; Giaouris et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that when hfq was deleted, the expression of many enterotoxin genes in bacteria, such as nheA , nheB , entFM , entD 1, entD 2, and hbl C, was significantly increased at the transcriptional level ( Figure 6B ), which to some extent enhanced bacterial virulence ( de Maagd et al, 2003 ). In addition, the deletion of hfq also led to a significant increase in the amount of bacterial biofilm formation ( Figure 3B ), and the ability to form biofilms is also considered to be a key virulence factor in a variety of bacteria ( Ramírez-Larrota and Eckhard, 2022 ). Environmental adaptability can help bacteria resist antibiotics and the host’s immune system, which facilitates bacterial survival and infection in the host, ultimately leading to host death ( Al Safadi et al, 2012 ; Giaouris et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in biofilm formation ability after the mutation of ascO gene in this experiment needs further investigation. Studies have shown that the ability to form biofilms is considered to be a key virulence factor for a variety of bacteria (Ramirez‐Larrota & Eckhard, 2022). We hypothesized that the decreased biofilm formation ability of the mutant strain ∆ ascO was one of the factors contributing to its decreased virulence.…”
Section: Discussionmentioning
confidence: 99%
“…After attachment to the plasma protein-covered device is accomplished, bacteria grow by proliferation and produce polymeric molecules to form a scaffolding extracellular matrix ( Figure 1 ). Biofilm polymers include polysaccharides, proteins, extracellular DNA (eDNA), teichoic acids and other molecules on the whole constituting an aqueous gel-like material with proper mechanical properties and resistance to external shocks [ 91 ].…”
Section: Staphylococcal Biofilm Development On the Surface Of Biomate...mentioning
confidence: 99%